Eco Dakwah Dalam Meningkatkan Kepedulian Sosial di MI IT Nurul Ikhwan Cahaya Ananda Palembang - Romadhan, Wahyu (Program Studi Manajemen Dakwah, Fakultas Dakwah dan Komunikasi, UIN Raden Fatah Palembang, 2025)
This study explores the implementation of eco da’wah in improving students’ social awareness at MI IT Nurul Ikhwan Cahaya Ananda using a qualitative descriptive approach with data collected through observation, interviews, and documentation involving the principal, teachers, and students. The findings show that eco da’wah is implemented through school habituation programs, integration in Islamic education subjects, and social-environmental activities which contribute to improving students’ empathy, discipline, responsibility, and environmental awareness. The implementation is supported by school commitment, teacher involvement, and school culture, while limited facilities, inconsistent parental support, and varying teacher understanding become the main challenges. This study concludes that eco da’wah is an effective approach to strengthen character education and social concern in Islamic elementary schools and should be developed as a sustainable educational model